SG2-Type R2R3-MYB Transcription Factor MYB15 Controls Defense-Induced Lignification and Basal Immunity in Arabidopsis - Chezem, William R; Memon, Altamash; Li, Fu-Shuang; Weng, Jing-Ke; Clay, Nicole K (The Plant cell, 2017)
Lignification of cell wall appositions is a conserved basal defense mechanism in the plant innate immune response. However, the genetic pathway controlling defense-induced lignification remains unknown. Here, we demonstrate the SG2-type R2R3-MYB transcription factor MYB15 as a regulator of defense-induced lignification and basal immunity. Loss of MYB15 reduces the content but not the composition of defense-induced lignin, whereas constitutive expression of increases lignin content independently of immune activation. Comparative transcriptional and metabolomics analyses implicate as necessary for the defense-induced synthesis of guaiacyl lignin and the basal synthesis of the coumarin metabolite scopoletin. MYB15 directly binds to the secondary wall MYB-responsive element consensus sequence, which encompasses the AC elements, to drive lignification. The and lignin biosynthetic mutants show increased susceptibility to the bacterial pathogen , consistent with defense-induced lignin having a major role in basal immunity. A scopoletin biosynthetic mutant also shows increased susceptibility independently of immune activation, consistent with a role in preformed defense. Our results support a role for phenylalanine-derived small molecules in preformed and inducible Arabidopsis defense, a role previously dominated by tryptophan-derived small molecules. Understanding the regulatory network linking lignin biosynthesis to plant growth and defense will help lignin engineering efforts to improve the production of biofuels and aromatic industrial products as well as increase disease resistance in energy and agricultural crops.